Pengaruh Metode Bermain Untuk Meningkatkan Lari Sprint 30 Meter Kelas V Sdn Kedungwaringin 01 - Dwinanda, Mochamad Agung; Nugroho, Setio; Yuda, Arya Kusuma (Peneliti.net, 2025)
The background of this study is the lack of student activity in the learning process of Physical Education sprint running. This study aims to determine the effect of the play method to improve the 30-meter sprint of class V SDN Kedungwaringin 01. Using a one-group pre-test-post-test design, this study employs an experimental methodology with a sample of 56 elementary school students in the fifth grade. Eight surveys were administered in class V at SDN Kedungwaringin 01. The results of the survey and data analysis show that in the pretest and posttest, the impact of the play method on improving the 30-meter sprint improved by 13.04 and 26.75 points, respectively. The Paired Sample T-Test table yielded a sig (0.001) and a t-count value of 52,566. Thus, it can be said that class V SDN Kedungwaringin 01's 30-meter sprint has improved considerably as a result of the play method's use.